A fabricação do teatro brasileiro moderno: "Vestido de noiva" e a crítica teatral - 1928-1948 - Henrique Brener Vertchenko (2016)
Considering the theatrical spectacle Wedding Dress, by Nelson Rodrigues, and your big event status for the modernization of theater in Brazil, this study analyzes the processes of legitimacy involved in the construction of this mark, with special emphasis given to the printed theater critic. First performed at the “Teatro Municipal” of Rio de Janeiro in December 1943 by the amateur group Os Comediantes, the play figured in the history of Brazilian theater, and also in the national imaginary, as a founding event for the modernization of our performing arts. In order to understand the power lines involved in the construction of this inaugural mark, it sought to understand the role of the critic in formation and consolidation of Brazil's image as a producer country of a modern theater, in a period from 1928 to 1948. We argue, therefore, that there was a process of building a cultural symbolic fine for an intellectual milieu that, through their critics, developed important standards and origin myths to the formation of aspects of national identity. These critics were woven amid conflicts that put in different theater projects for the nation, whose paths were incited with the action of the state and intellectuals, many from modernist ranks, as well as professional theatrical organizations members. Facing the modern theater in Brazil as a national project, I analyze the critical reception of Nelson Rodrigues play as privileged scriptures to understand the debates on the modernization of our theater, emphasizing the legitimizing role played by "literary critics" and conceiving the critic as multiple textual category that provides a history of the theater as one way of reading history.